Evaluating the green and Ampt infiltration parameter values for tilled and crusted soils - Mohamoud, Y.M. (Elsevier, 1991)
Methods for determining Green—Ampt infiltration parameter values for tilled and crusted soils are not well established. A two-stage method is developed to determine the Green and Ampt parameter values for soils under different management practices. The first stage is aimed at calculating rainfall infiltration from rainfall and runoff data of small field plots which had different soil surface conditions (e.g. tillage, residue cover and crusting). To determine accurate rainfall infiltration rates from field plots, we employed a water balance model which accounted for depression storage, detention storage as well as surface routing of runoff. The second stage is aimed at evaluating the values of the Green and Ampt infiltration equation parameters by the linear least squares parameter estimation technique. The Green and Ampt parameter values determined were the effective capillary suction at the wetting front and the effective hydraulic conductivity.